SAW and Electre Methods Implementation for Scholarship Awardee Decision - Siregar, Victor (Internet of Things and Artificial Intelligence Journal, 2021)
This research was conducted to design a Decision Support System as a tool for decision-makers in distributing Bidik Misi Scholarships at the Indonesian Business Polytechnic. The selection of students who volunteered to become recipients of the Bidik Misi Scholarship required the Decision Support System (DSS) approach which implemented the Simple Additive Weighting (SAW) method by weighting the criteria and sub-criteria of each alternative for all attributes. The criteria used in the SAW method in this study consisted of 2 (two) criteria and each of these criteria had sub-criteria. The first criterion is Parents with sub-criteria consisting of the education level, incomes, parents’ coverage. The second criterion is students with sub-criteria consisting of age, academic potential, ownership of the Indonesia Smart Card (KIP). The output obtained from the 5 data analyzed in this study, the final value of the highest alternative preference is 0.9 and the lowest alternative preference value is 0.55. The output obtained by using the Electre method is that the Student_Mari004 alternative eliminates other alternatives.